Organizational Climate and its Connection to Job Performance in a Mining Company. The Case of Shougang - Mallma Chuquillanqui, Juan José (2023)
The aim of this paper is to determine the relation between organizational climate and worker performance in Shougang Hierro Perú, Marcona, 2019-2021. This research is correlational and has a non-experimental design. The population consisted of 150 workers, and a sample of 120 individuals was considered. The instrument chosen for measuring the independent variable, organizational climate, was a 40-item questionnaire; on the other hand, the dependent variable, job performance, was measured through the performance evaluation sheet used by the company. The statistical software IBM SPSS 25.0 was used for the analysis. The general hypothesis was accepted and had a correlation value of 0.953, meaning a very high positive correlation and determining that there is a highly significant relation between organizational climate and the workers' job performance. It can be concluded that a good organizational climate helps achieve a better worker performance. In addition, the relevant correlations leading to an improvement in the mining company's organizational climate have been identified.